1988
DOI: 10.1161/01.hyp.11.2.160
|View full text |Cite
|
Sign up to set email alerts
|

Enalapril attenuates natriuresis of atrial natriuretic factor in humans.

Abstract: . Under these conditions baseline sodium excretion was not different from the control study, but it rose less after ANF (from 117 ± 22 to 242 ± 63 /umol/min), and the increments in glomerular nitration rate, free water clearance, phosphate, lithium, uric add, and magnesium were all blunted and nonsignificant. In addition, effective renal plasma flow tended to fall; this effect was not observed when ANF was given without enalapril. These results support the notion that the effects of ANF on renal hemodynamics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

1989
1989
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 31 publications
1
22
1
Order By: Relevance
“…Despite this close relationship, few studies have been reported in the literature on the effects of blockade of the renin-angiotensin-aldosterone system by converting enzyme inhibitors on the pharmacological actions or plasma levels of ANP. It has been shown in Wistar rats that the natriuretic action of infusion of ANP is not influenced by pretreatment with captopril (Hirata et al, 1987). Data on the influence of converting enzyme inhibition on the hypotensive effect of an ANP infusion are inconsistent since both a potentiation (Awah et al, 1986) and no effect (Hirata et al, 1987;Hansell & Ulfendahl, 1987;Gaillard et al, 1988) have been reported. Finally, it has recently been shown in humans that the vasodilatory effect of an intra-arterial infusion of ANP is not influenced by pretreatment with captopril (Hughes et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this close relationship, few studies have been reported in the literature on the effects of blockade of the renin-angiotensin-aldosterone system by converting enzyme inhibitors on the pharmacological actions or plasma levels of ANP. It has been shown in Wistar rats that the natriuretic action of infusion of ANP is not influenced by pretreatment with captopril (Hirata et al, 1987). Data on the influence of converting enzyme inhibition on the hypotensive effect of an ANP infusion are inconsistent since both a potentiation (Awah et al, 1986) and no effect (Hirata et al, 1987;Hansell & Ulfendahl, 1987;Gaillard et al, 1988) have been reported. Finally, it has recently been shown in humans that the vasodilatory effect of an intra-arterial infusion of ANP is not influenced by pretreatment with captopril (Hughes et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, the magnitude of this attenuation was comparable with that seen in our previous study, where the subjects consumed only 100 mmol sodium daily. 5 Apparently, a 300 mmol sodium diet, as supplied in the present study, does not suppress the renal renin-angiotensin system to the extent of eliminating the effects of converting enzyme inhibition on the kidney. The data on lithium, free water clearance, and excretion of other electrolytes are compatible with less suppression by ANF of (fractional) tubular solute reabsorption at proximal and distal nephron segments during converting enzyme inhibition than before converting enzyme inhibition.…”
Section: Discussionmentioning
confidence: 55%
“…Wilkins et al 12 employed short-term (15 minutes), high-dose infusions of ANF and reported a nonsignificant trend toward higher intrainfusion plasma ANF values. Gaillard et al 14 gave bolus injections of ANF (100 ^g) and reported a similar, slight, and statistically insignificant trend toward higher peak ANF values after enalapril. We chose a dose (1.5 pmol/kg/min) and duration (3 hours) of ANF that induced plasma ANF concentrations within the lower part of the clinical pathophysiological range, 2223 which allowed steady-state values of plasma ANF to be established, and which is known to exert biological effects, 24 -26 including natriuresis.…”
Section: Discussionmentioning
confidence: 77%
“…Gaillard et al 14 documented a shift in baseline PAH clearance between study days, further adding to difficulty in interpretation of data from that study.…”
Section: Ns Nsmentioning
confidence: 91%